Modelo de decisão multicritério para seleções interciclo das universidades novas: estudo na Universidade Federal do Rio Grande do Norte - Aires, Renan Felinto de Farias (2014)
The discussions wherein develop proposals for university reform in Brazil include, among other things, the conception of the university titled "New University", whose structural origin comes from the bill of higher education reform and unification of the foundations of education European upper (Bologna process). At its core, the Bologna process has imposed a series of transformations, among which, the promotion of mobility, as a stimulus to interinstitutional cooperation to enable an better and bigger qualification of the students. Nevertheless, what we see is that this point is one of the main points made flawed by Brazilian institutions that have adopted this model of higher education. An example is the Bachelor of Science and Technology - BC&T, Federal University of Rio Grande do Norte - UFRN, where there are problems of the internal order, represented by the problem of the reusing of the disciplines, such also of external order, in cases of transfers interinstitutional. Because of this, and knowing that this is a typical problem in which multiple criteria are involved, the aim of this study is to propose a multicriteria model for selection of interciclo of the BC&T of the UFRN which addresses the issue of mobility. For this, this study was of exploratory and study case nature, use as tools of data collection, the bibliographic and documentary research, as well as semi-structured interviews. For the elaboration of the model, were used the five phases most commonly used in the modeling of problems in operational research in a sample of 91 students of BC&T. As a result, we obtained a model that addresses the issue of internal and external mobility of the school and that, moreover, was also more robust and fair than the current model of BC&T and also what is used in other courses of the UFRN, taking into consideration the expected results by the decision makers